Implementasi Ekstrakurikuler Jarimatika Dalam Menumbuhkan Kemampuan Berhitung Pada Kelompok A Di TK Bunga Harapan Bringin - Ani Fitriati; Mustakimah Mustakimah (UIN Sultan Maulana Hasanudin Banten, 2024)
Counting ability is one of the abilities that needs to be grown early, especially in group A children, because counting will make it easier for children to understand the concept of numbers, which cannot be separated from everyday life. Learning in early childhood must be real (concrete) because at this age it is the pre-operational stage. This study aims to determine how the implementation of extracurricular jarimatika in fostering counting skills in early childhood at Bunga Harapan Kindergarten. The type of research used is descriptive qualitative research with data collection techniques through observation and documentation. The subjects of this study were children in group A of Bunga Harapan Bringin Kindergarten, totaling 19 students, 10 girls and 9 boys. The results showed that jarimatika extracurricular activities were less effective in fostering counting skills in group A children at Bunga Harapan Kindergarten.